Effectiveness of smoking cessation interventions: review of evidence and implications for best practice in Australian health care settings - Margaret Miller; Lisa Wood (Elsevier, 2003)
Abstract Objective:To review the evidence of the effectiveness of various smoking cessation methods and appropriateness for use in Australian health care settings. Methods:Cochrane and other existing reviews and meta‐analyses of evidence were the basis for the review. Systematic literature searches were also conducted to identify relevant controlled trials published internationally between January 1999 and May 2002. The main inclusion criteria for studies were use of a controlled evaluation design and an outcome measure of continuous abstinence from smoking for at least five months. A three‐tiered grading system for strength of evidence was used. Results:Clinic and hospital systems to assess and document tobacco use and routine provision of cessation advice can double long‐term quit rates. While brief intervention can achieve a significant effect at population level, at individual level there is a strong dose response between the number and length of sessions of tobacco cessation counselling and its effectiveness. Effective behavioural interventions can increase cessation rates by 50-100% compared with no intervention. Some pharmacotherapies are safe and also help to substantially increase cessation rates. Conclusions:Effective behavioural and pharmacological methods of tobacco cessation are available. Implications:Every smoker should be offered evidence‐based advice and treatment to quit smoking. This includes pharmacotherapy, unless contra‐indicated. Health professionals and health care settings can play a significant role in motivating and assisting smokers to quit.